Rhinovirus persistence during the COVID‐19 pandemic—Impact on pediatric acute wheezing presentations. Issue 11 (21st July 2022) - Teo, Kah Wee; Patel, Deepa; Sisodia, Shilpa; Roland, Damian; Gaillard, Erol A.; Tang, Julian W.
Abstract: Rhinoviruses have persisted throughout the COVID‐19 pandemic, despite other seasonal respiratory viruses (influenza, parainfluenza, respiratory syncytial virus, adenoviruses, human metapneumovirus) being mostly suppressed by pandemic restrictions, such as masking and other forms of social distancing, especially during the national lockdown periods. Rhinoviruses, as nonenveloped viruses, are known to transmit effectively via the airborne and fomite route, which has allowed infection among children and adults to continue despite pandemic restrictions. Rhinoviruses are also known to cause and exacerbate acute wheezing episodes in children predisposed to this condition. Noninfectious causes such as air pollutants (PM2.5, PM10 ) can also play a role. In this retrospective ecological study, we demonstrate the correlation between UK national sentinel rhinovirus surveillance, the level of airborne particulates, and the changing patterns of pediatric emergency department presentations for acute wheezing, before and during the COVID‐19 pandemic (2018–2021) in a large UK teaching hospital.